Recovery from anorexia nervosa: the influence of women's sociocultural milieux. (October 2021) - Allison, Stephen; Warin, Megan; Bastiampillai, Tarun; Looi, Jeffrey C L; Strand, Mattias
Objective: Young women living in industrialised westernised societies have a higher prevalence of anorexia nervosa, partly due to a cultural emphasis on thinness as a beauty ideal. Sociocultural milieux might promote recovery from anorexia nervosa amongst young women. The current article is a commentary about the social influences on recovery from anorexia nervosa – based on social anthropology, narratives of people with lived experience, and clinical studies. Conclusion: Anorexia nervosa increases social withdrawal, and recovery leads to re-engagement with meaningful relationships. Recovery also empowers women as 'cultural critics' who challenge assumptions about the thinness beauty ideal and gender roles. The gradual process of full or partial recovery often occurs during emerging adulthood (aged 20–29). In this life stage, adolescent friendship groups are dissolving as women move from education to work, reducing the danger of weight-based teasing by peers, which is an environmental risk factor for disordered eating. Women recovering from anorexia nervosa may connect with those aspirations of peers and mentors that eschew a focus on weight and shape, but relate to the life-stage tasks of starting careers, beginning new friendships, selecting life partners and family formation – that is, a broader role in larger relationship networks.